(untitled) (Bangladesh Journal of Medical Science, 2020)
Objective: The effect of Pimpinela alpina Molk (PaM) on decrease in Bax and Caspase-3 protein expression in liver cells apoptosis have been proven. However, the difference result between 7 and 15 days treatment duration of PaM need to be confirmed. This study aimed to confirm that treatment of PaM during 15 days is more effective decreasing Bax and Caspase-3 protein expression in liver cells following UVB irradiation. Methods: In the post test only control group design, 35 Sprague Dawley male rats, 300 gram body weight were divided into two arms, consisting of three groups respectively. First arm comprise Neg-7, PaM7-100, and PaM7-150. Second arm comprise Neg-15, PaM15-100, and PaM15-150. Nor-G was added as normal control neither exposed to UVB nor PaM treatment. In negative group was only radiated to UVB and PaM groups were exposed to UVB and treatment with 100, and 150 mg PaM per oral for 7 and 15 days respectively. At day 8 (first arm) and 16 (second arm), liver organ was taken and Bax and Caspase-3 protein expression assessed by Immunohistochemical staining method. Result: Post Hoc LSD analysis indicated that Bax and Caspase-3 protein expression in PaM15-100 and PaM15-150 was significant lower compared to that of Nor-G, PaM7-100, and PaM7-150, p < 0.05. Conclusion: Ttreatment of PaM with doses 100 and 150 mg for 15 days was better in decreasing Bax and Caspase-3 protein expression of liver cells following UVB irradiation. Bangladesh Journal of Medical Science Vol.19(2) 2020 p.296-303